Patient Safety in Surgery - Stahel, Philip F.; Mauffrey, Cyril (Springer London : Imprint: Springer, 2014)
Covering all aspects related to patient safety in surgery, and aiming to increase the safety and quality of care for patients undergoing surgical procedures in all fields of surgery, Patient Safety in Surgery is the perfect book for medical professionals striving to achieve excellent results and ideal patient outcomes. Adverse events resulting from surgical interventions frequently related to system errors and a communication breakdown among providers are looked at, in order to help the reader in dealing and avoiding these risky situations.   Presenting pertinent issues of interest in complications and patient outcomes, Patient Safety in Surgery is aimed at surgeons, anesthesiologists and medico-legal experts. It will also be of interest to medical trainees (students, residents, and fellows), nurses, patients, patient's families, and advocacy groups.